IMPLEMENTASI KEBIJAKAN PERDA KOTA SURABAYA NO. 8 TAHUN 2012 TENTANG RETRIBUSI PELAYANAN PARKIR DI TEPI JALAN UMUM - Susanto, Luqman Eko (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
The implementation of the policy of Surabaya City regulation number 8 year 2012 on retribution of parking service at public roadside. This thesis discusses the implementation of the policy regulation on the edge of the parking service levies a public road Surabaya. The method used is the type of qualitative descriptive study. Data collection is done by means of surveys, interviews, observation. Results from this study showed in the implementation of parking policy implementation Bank Pulic Road was less successful. The problems are: (1) The emergence of illegal parking attendant; (2) The parking rates are not in accordance with predetermined; (3) The issue of tickets; (4) Problems attributes parkirng attendant uniforms and equipment; (5) The parking lot is irregular and (6) Lack of knowledge of the parking attendant to the local regulations and how to mange traffic. Efforts to resolve the issue UPTD Perparkiran Surabaya perform the steps are: (1) curbing illegal parking by conducting joint operations carried out erery 1 (one) month three (3) times in a month involving an element of police, UPTD Parking Transportation Department, Civil Service Police Unit, prosecutors, courts; (2) To examine the Tand a Member Card (KTA); (3) Confirm the problems that exist for entrepreneurs that parking in the area; (4) Parking wild that do not want to pay the levy arrested to be followed in accordance with applicable regulations; (5) Provide guidance on the procedures set up / organize parking, as well as provide guidance on how to set up traffic to the parking attendant; (6) CoordinateÂ  related parties to the arrangement and the arrangement of the park in the city of Surabaya. Â  Keywords:Policy Implementation, Levy Parking